Post-Covid-19 Disposible Income Resistance Against Community Welfare In Regency Aceh Singkil - Rosliana, Rosliana; Khamilah Siregar, Oktarini; Azwar Hasibuan, Hasrul; Hidayat, Rahmat; Samrin, Samrin; Suhendi, Suhendi; Novalina, Ade (Publisher Cv. Inara, 2022)
The purpose of the study was to examine how much resilience the community's disposable income was due to COVID-19, and the factors for increasing farmer productivity in Tanah Bara Village, Gunung Meriah District based on the SEM model. The main problems studied are the decline in the resilience of disposable income due to lack of capital in opening wider agricultural land, soil fertility which is increasingly polluted which causes unable to cultivate crops, narrow land cannot increase the area of ??land owned, seed quality is not good. which causes crop failure or poor yields, the number of plant pests that cause death and does not produce and the lack of human resources in agricultural and plantation management The analytical model used in Confirmatory Factor Analysis (CFA) to see the causal effect of several independent variables, namely the quality of fertilizer , capital, soil fertility, seed quality, technology, pests, number of workers to increase farmer productivity in Tanah Bara Village, Gunung Meriah District. The results showed that there were 3 factors that influenced the income and welfare of the community, namely factor 1 which consisted of the quality of fertilizer, capital, soil fertility and labor. Factor 2 which consists of seed quality and technology and factor 3 which consists of pests.